Investigation of tribological, physicomechanical, and morphological properties of resin-based friction materials reinforced with Agave americana waste. (23rd July 2021) - Wu, Siyang; Zhuang, Jian; Wu, Qian; Qi, Hongyan; Zhao, Jiale; Guo, Mingzhuo
Abstract: In recent years, natural fibers and their composites have attracted the attention of researchers due to environmental awareness and sustainable development. It is crucial to identify new natural fibers as potential reinforcement in polymer composites. This study was aimed to investigate the potential use of Agave americana fibers as a reinforcing component in resin-based friction materials. The tribological, physicomechanical, and morphological characteristics of materials containing different A. americana fiber contents were systematically evaluated. Experimental results indicated that fiber addition effectively improved the fade resistance, recovery behavior, and wear resistance of these materials. From the perspective of overall performance, a friction composite containing 5-wt% fibers possessed the optimal friction stability and wear resistance, exhibiting a fade rate of 13.6%, recovery rate of 97.5%, and sum wear rate of 2.340 × 10 –7 cm 3 ·N −1 ·m −1 . Furthermore, sample worn surface morphologies were examined by scanning electron microscope, which revealed that appropriate fiber inclusion helped in the formation of secondary contact plateaus on friction surfaces. In addition, this fiber content significantly reduced abrasive and adhesive wear, which were conducive to good tribological behaviors of friction materials. This research provided a promising method for environment-friendly applications of A. americana waste.